European dietitians as key agents of the green transition: An exploratory study of their knowledge, attitudes, practices, and training - Muñoz-Martínez, Júlia; Carrillo-Álvarez, Elena; Janiszewska, Katarzyna (Frontiers in Nutrition, 2023)
How food systems are currently provisioning food to the population is a matter of debate worldwide. Food systems, driven by widespread and increasing adherence to a westernized dietary pattern, are failing to meet people’s basic needs and are draining natural resources. There is a push to make food systems more healthy, fair, and sustainable. To this end, action from all players is needed to meet the international agenda. In this regard, dietitians play a crucial role, as they provide advice and promote actions that foster the adoption of more sustainable dietary patterns as well as the promotion of sustainable food systems. As an emerging requirement in their training, it is crucial that dietitians are aware of their role in this transition. For this reason, the aim of the present study is to explore the knowledge, attitudes, practices, and training (KAPT) of European dietitians on sustainable dietary patterns (SDP) by administering an online survey. Responses from 2211 dietitians from 25 countries were received between April 2021 and August 2021. Results show that European dietitians are lacking training on SDP but are willing to learn more about it. Most dietitians perceive themselves as able to define an SDP, although aspects concerning social and economic sustainability were underestimated. Dietitians concur that barriers exist to the promotion of SDP, such as the lack of updated national food-based dietary guidelines and the absence of support from peers and managers. The country of professional activity seemed to be key to influencing dietitians’ KAPT. These results emphasize the need to strengthen European dietitians’ training in SDP and increase public and private commitment to consider dietitians as key professionals for the transition towards sustainable food systems.